The effect of irrigated rice cropping on the alkalinity of two alkaline rice soils in the Sahel - Asten, Piet J.A. van; Van't Zelfde, J.A.; Zee, A. van der; Hammecker, C. (Elsevier, 2004)
Irrigated rice cropping is practiced to reclaim alkaline-sodic soils in many parts of the world. This practice is in apparent contrast with earlier studies in the Sahel, which suggests that irrigated rice cropping may lead to the formation of alkaline-sodic soils. Soil column experiments were done with some of Sahel's most alkaline-sodic rice soils from the Office du Niger (Mali) and Foum Gleita (Mauritania). Soils were irrigated using non-saline carbonate-rich irrigation water typical for the Sahel and percolation was maintained at 3–4 mm day−1. After one cropping season, soils had turned from sodic to non-sodic, and pH had dramatically decreased, most notably in the upper soil layers. The changes were most important in the Office du Niger soil due to its small buffering capacity (small CEC and CaCO3). Alkalinity consumed by above-ground matter of the rice plants (grain and straw) equaled or exceeded alkalinity added via irrigation in a zero percolation scenario. Hence, for a climate and irrigation water that are typical for the Sahel, removal of straw and grain prevents or substantially reduces further alkalinization of the soils if percolation is absent. However, in case of some percolation, straw can best be incorporated in the topsoil of calcareous soils as it accelerates de-alkalinization and de-sodication through increased dissolution of calcite. No evidence was found indicating that ferrolysis altered the short-term alkalinity balance of the studied soils to any extent. Our results are in line with recent field studies and suggest a de-alkalinization of sodic-alkaline flooded (rice) soils in the Sahel.